Pembangunan Fondasi Keagamaan Islam Pada Anak Usia Dini - Iwan Ridwan; Jakaria Jakaria; Wardatul Ilmiah; Ima Maisaroh; Siti Muhibah; Ratu Amalia Hayani (UIN Sultan Maulana Hasanuddin Banten, 2021)
Children are individuals who are experiencing development. Early childhood is an individual who is at the golden age stage where at this time the child is experiencing a high sense of curiosity about something as learning. The formation of superior human character is an all-time project in Islam. Therefore, in this paper, the author wants to find the right steps to build a religious foundation in children whose ending will develop into characters that reflect behavior based on religious values.The results of this study indicate that (1) the religious values instilled in children are the values of faith, morals and worship. (2) a) The methods used are modeling, habituation, parables, storytelling and dialogue. b) The results obtained are that the child is able and accustomed to praying without coercion, becomes accustomed to learning the Koran, loves Allah's creation and does good deeds. c) Other family members also have a share. d) The process is carried out anywhere and anytime. (3) Parents act as father and mother as well as friends. (4) The family environment and social environment have an influence on the process of cultivating religious values. (5) a) The supporting factors are the family environment and places of worship in the house. b) The inhibiting factor is the child's social environment and the limited time the parents have. Solutions to overcome inhibiting factors are to supervise children, reduce or limit children's play hours, and give advice to children. Keywords: Religious Foundation; Early childhood; FamilyReferencesAbdul Rahman Saleh. (2000). Pendidikan Agama dan Keagamaan, Visi, Misi, dan Aksi. Gemawindu Pancaperkasa. Abu Amr Ahmad Sulaiman. (2005). Metode Pendidikan Anak Muslim Usia 6-9 Tahun. (Alih bahasa: Luqman Hakim). Jakarta: Darul Haq. Arif Rohman. (2009). Memahami Pendidikan dan Ilmu Pendidikan. Laksbang Mediatama. C. Asri Budiningsih. (2008). Pembelajaran Moral Berpijak pada Karakteristik Siswa dan Budayanya. PT Rineka Cipta. Euis Sunarti. (2004). Mengasuh dengan Hati. PT Elex Media KomputIndo Gramedia. Fauziddin, M. (2016). Pembelajaran Agama Islam Melalui Bermain pada Anak Usia Dini (Studi Kasus di TKIT Nurul Islam Pare Kebupaten Kediri Jawa Timur). Hisyam, M. R., Suyanto, Sadzili, M., Arifin, Z., & Rahman, A. S. (2019). Peran Anggota Keluarga Berketahanan Dalam Perspektif Quran. Ulumuddin: Jurnal Ilmu-ilmu Keislaman, 9(2), 171–186. Hurlock, E.B. (1978). Perkembangan Anak. (Alih bahasa: Meitasari Tjandrasa). Erlangga PT Gelora Aksara Pratama. Imroatun, I., Nirmala, I., Juhri, J., & Muqdamien, B. (2020). Kajian Literatur Pengasuhan Anak Usia Dini Dalam Islam. As-Sibyan: Jurnal PAUD, 5(1), 57–66. Kurnia, Y. (2015). Pengembangan Kemampuan Ajaran-ajaran Agama dan Moral di TK. Bandung: PPPPTK TK dan PLB. Ngaisah, S. (2018). Pendidikan Agama Islam Bagi Anak Usia Dini Melalui Pembelajaran Sentra. As-Sibyan : Jurnal PAUD, 3(1), 15–24. Mansur. (2005). PAUD dalam Islam. Pusaka Pelajar. Meggit Carolyn. (2013). Memahami Perkembangan Anak. (Alih bahasa: Agnes Theodora W). PT Indeks. Muh. Nur Mustakim. (2005). Peranan Cerita Dalam Pembentukan Perkembangan Anak TK. Jakarta: Direktur Pembinaan Pendidikan Tenaga Kependidikan dan Ketenagaan Perguruan Tinggi. Muhammad Azmi. (2006). Pembinaan Akhlak Anak Usia Pra Sekolah. Penerbit Belukar. Muhammad Fadillah & Lilif Maulifatu Khorida. (2013). Pendidikan Karakter Anak Usia Dini. Ruzz Media. Nadjih, D., & Imroatun, I. (2016). Hadits Tentang Pendidikan Jasmani Anak Usia Dini. Prosiding Seminar Nasional Peran Pengasuhan Anak Raudhatul Atfal Dalam Membangun Karakter Bangsa, 51–64. Najamuddin Muhammad. (2011). Tips Membuat Anak Rajin Ibadah Sejak Dini. Sabil. Ngaisah, S. (2018). Pendidikan Agama Islam Bagi Anak Usia Dini Melalui Pembelajaran Sentra. As-Sibyan : Jurnal PAUD, 3(1), 15–24. Rahayu, S. H., Haroen, H., Budiutomo, T., Khasanah, N., & Nuryati. (2020). Manajemen Mutu Layanan Ta’lim Quran lil Aulad (TQA) di Yayasan Team Tadarus “AMM” Yogyakarta. Nuansa Akademik: Jurnal Pembangunan Masyarakat, 5(2), 117–130. Rahman, H. S. (2002). Konsep Dasar PAUD. PGTKI Press. Rahmawati, A. Y. D., Nasruddin, M., & Imroatun, I. (2020). Peran Sosial Guru Pendidikan Agama Islam Di Wilayah Pesisir Utara Pulau Jawa Nuansa Akademik: Jurnal Pembangunan Masyarakat, 5(1), 1–12. https://doi.org/10.47200/jnajpm.v5i1.417Rizki Ananda, Implementasi Ajaran-ajaran Moral dan Agama pada Anak Usia Dini, Jurnal Obsesi, Volume 1 Issue 1 (2017) Pages 19 – 31. Sjarkawi. (2006). Pembentukan Kepribadian Anak, Peran Moral, Intelektual, Emosional, Sosial sebagai Wujud Integritas Membangun Jati Diri. Bumi Aksara. Sugiyono. (2005) Memahami Penelitian Kualitatif. Alfabet. Undang-Undang Republik Indonesia Nomor 20 Tahun 2003 Tentang Sistem Pendidikan Nasional, (2003). Uyuni, Y. R. (2019). Konsep Pola Asuh Orang Tua Dalam Perspektif Islam Terhadap Tumbuh Kembang Anak Dalam Keluarga. aṣ-ṣibyān: Jurnal PAUD, 4(1), 53–64.